The relationship between periodontite and diabetes mellitus type ii facing the new classification of periodontal diseases: literature review - OLIVEIRA,Lívia Maria Lopes de (2020)
ABSTRACT Periodontal disease and type 2 diabetes mellitus are considered chronic diseases that at their core have a deep relationship with inflammation. It is assumed that there is a bidirectional relationship between periodontal disease and type 2 diabetes mellitus. It is estimated that approximately 10% of the world’s population is affected by periodontal disease, in its most severe form, almost the same percentage estimated for people with diabetes, which is considered a 21st century emergency. The World Workshop for the Classification of Periodontal and Peri-implant Diseases and Conditions took place from September 9-11, 2017. The aim of this study is to analyze the results of this workshop with regard to the relationship between periodontal diseases/conditions and diabetes mellitus, in addition to conducting an integrative review on the topic. A literature review was conducted, using the Medline electronic databases via Pubmed, Scientific Electronic Library Online, Scientific and Technical Literature of Latin America and the Caribbean and Virtual Health Library. A new classification of periodontal disease included tools for individual assessment of the patient and recognizing risk factors that might negatively interfere in response to treatment. The occurrence of metabolic lack of control in periodontal patients with type 2 diabetes mellitus is now considered a factor of great importance for the assessment of individual susceptibility to the progression of periodontitis. Diabetes is believed to promote a hyper inflammatory response to bacterial challenge by modifying the tissue response of periodontal tissues.